Robot Vehicle Platoon Experiment Based on Multi-leader Vehicle Following Model - Kita, Eisuke; Sakamoto, Hiroki; Takaue, Hiroto; Yamada, Miichiro (2014 Second International Symposium on Computing and Networking, 2014)
The velocity control algorithm of vehicles in vehicle platoon is applied for the platoon experience of the vehicle robots. Stability analysis of the models is performed to determine the parameters and then, the summation of sensitivities for all leader vehicles is maximized. The results show that the velocity control can be performed by the velocities of only one or two leader vehicles, the nearest leader vehicle and the lead vehicle of the platoon. The model is applied for the velocity control of the vehicle robots in the vehicle platoon. The experimental result is compared with the numerical simulation in order to confirm the validity of the model. The experimental result qualitatively agrees with the computer simulation.